Catalytic phosphonylation of C=X electrophiles - Kolodiazhna, O.O.; Gryshkun, E.V.; Kolodiazhna, A. O.; Sheiko, S.Yu.; Kolodiazhnyi, O.I. (Reports of the National Academy of Sciences of Ukraine, 2020)
A method for the catalytic phosphonylation of C = X electrophiles has been developed. Pyridinium perchlorate is an effective catalyst for the phosphonylation reaction of trialkyl phosphites with various electrophiles C = X (X = O, S, N). The reaction leads to the formation of corresponding α-substituted phosphonates in high yields. The reaction leading to the formation of bisphosphonates represents the highest interest. It was found that the nucleo philic attack of triethyl phosphite on the electron-deficient carbon of the C = X group leads to the formation of beta ine, which reacts with pyridinium perchlorate to form alkoxyphosphonium perchlorate and pyridine. Quasiphosphonium salt is unstable and decomposes to form phosphonate, alkene, and perchloric acid, which reacts with pyridine to regenerate pyridinium perchlorate. The intermediate formed from the pyridinium halide decomposes to form alkyl halide. The general strategy of the proposed method for introducing phosphonate groups into a polyprenyl mole cule consisted in the sequential treatment of hydroxyl-containing a compound with the Swern reagent with the con version of the C—OH group into a carbonyl one. Subsequent phosphonylation of the carbonyl-containing interme diate with the reagent (EtO)3P/[PyH] + ClO 4– leads to the formation of hydroxyalkylbisphosphonate. The synthe sized prenyl bisphosphonates have a pronounced biological activity. These include, for example, enolpyruvylshikimate-3- phosphate synthase (EPSP), farnesyl protein transferase (FPTase), as well as HIV protease, which are of interest as potential biologically active substances.